Evolution and prehistory : (Thomson Wadsworth, 2008)
Explore evolution and prehistory through photos, examples, and anthropologists' studies with Haviland et al's EVOLUTION AND PREHISTORY. The authors' goal in writing this book is to provide you with a vivid, accessible text that shows how the field is relevant to understanding the complex world around you. With Haviland et al, you will have the opportunity to explore the different ways humans face the challenge of existence, learn about the connection between biology and culture in shaping human beliefs and behavior, and see the impact of globalization on peoples and cultures around the world.